2021
DOI: 10.3389/fnagi.2021.614809
|View full text |Cite
|
Sign up to set email alerts
|

Effects of White Matter Hyperintensities on Verbal Fluency in Healthy Older Adults and MCI/AD

Abstract: BackgroundWhite matter hyperintensities (WMHs) are markers for cerebrovascular pathology, which are frequently seen in patients with mild cognitive impairment (MCI) and Alzheimer’s disease (AD). Verbal fluency is often impaired especially in AD, but little research has been conducted concerning the specific effects of WMH on verbal fluency in MCI and AD.ObjectiveOur aim was to examine the relationship between WMH and verbal fluency in healthy old age and pathological aging (MCI/AD) using quantified MRI data.Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 91 publications
0
0
0
Order By: Relevance
“…As a high-risk state for developing AD, MCI is also characterized by histopathological changes of the brain, impaired cholinergic system, Aβ deposition, cerebrovascular changes, and age-related deterioration of learning and memory but does not affect daily life [7]. Previous studies suggested that "middle-aged" SAMP8 mice were a suitable model for basic MCI research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a high-risk state for developing AD, MCI is also characterized by histopathological changes of the brain, impaired cholinergic system, Aβ deposition, cerebrovascular changes, and age-related deterioration of learning and memory but does not affect daily life [7]. Previous studies suggested that "middle-aged" SAMP8 mice were a suitable model for basic MCI research.…”
Section: Discussionmentioning
confidence: 99%
“…SAMP8 is a spontaneous animal model characterized by age-associated pathologies in the hippocampus and other brain regions, including Aβ deposits, tau hyperphosphorylation, inflammation, endoplasmic reticulum stress, and neuronal injury [7]. Since all these changes resemble AD pathology, SAMP8 mice can be used as models for studying cognitive decline with aging.…”
Section: Introductionmentioning
confidence: 99%